2018
DOI: 10.3390/ma11040583
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Strength-Toughness-Hardness Balance in Large Cross-Section 718H Pre-Hardened Mold Steel

Abstract: The strength-toughness combination and hardness uniformity in large cross-section 718H pre-hardened mold steel from a 20 ton ingot were investigated with three different heat treatments for industrial applications. The different microstructures, including tempered martensite, lower bainite, and retained austenite, were obtained at equivalent hardness. The microstructures were characterized by using metallographic observations, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Simultaneously, Tu [ 15 ] also indicated that the lower bainite obtained via austempering had a higher tensile strength and toughness than tempered martensite in the case of JIS SK5 tool steel. Liu [ 16 ] and Hoseiny [ 8 ] studied the microstructure and mechanical properties of modified AISI P20 mold steel after austempering at 320 and 335 °C, respectively. Martensite/bainite multiphase microstructure was formed at both temperatures, but the morphology of bainite was coarse block.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, Tu [ 15 ] also indicated that the lower bainite obtained via austempering had a higher tensile strength and toughness than tempered martensite in the case of JIS SK5 tool steel. Liu [ 16 ] and Hoseiny [ 8 ] studied the microstructure and mechanical properties of modified AISI P20 mold steel after austempering at 320 and 335 °C, respectively. Martensite/bainite multiphase microstructure was formed at both temperatures, but the morphology of bainite was coarse block.…”
Section: Introductionmentioning
confidence: 99%
“…When the tempering temperature was increased to 500 °C, M 3 C carbides were replaced by M 2 C carbides, and M 23 C 6 precipitated. Liu et al [ 14 ] deduced that the homogenization process and Q‐T process produced relatively high strength and toughness. M 3 C and M 23 C 6 carbides were precipitated at 540 °C, which played a crucial role in precipitation strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…A common goal of structural materials research is to prepare materials with high strength and high toughness. However, most strategies that can effectively increase strength may sacrifice ductility, which is the so-called “strength–ductility trade-off” phenomenon [1,2]. Controlling the distribution and organization of defects is considered to be one of the effective ways to solve this problem [3].…”
Section: Introductionmentioning
confidence: 99%